Clinical Features and Therapeutic Approach of Varicella Zoster in a Pediatric Patient at Way Laga Health Center, Bandar Lampung, Indonesia - Ringgo Alfarisi; Tri Aprilia Aisyah; Tri Marezha Balqis; Tria Zulfadlia; Syifa Syahirah Azzahra; Syerli Saputri (Biomedical Research and Theory Letters, 2025)
Varicella, or chickenpox, is an acute infectious disease caused by the Varicella-Zoster Virus (VZV), a DNA virus of the Herpesviridae family. Despite being generally self-limiting in children, varicella remains a major public health concern due to its high transmissibility and potential complications in vulnerable populations. In Indonesia, the incidence of varicella has increased in recent years, particularly among school-aged children, reflecting gaps in vaccination coverage and heightened community mobility following the COVID-19 pandemic. This research presents the clinical features and therapeutic approach of a pediatric patient with varicella treated at Way Laga Health Center, Bandar Lampung. A 6-year and 11-month-old boy developed fluid-filled lesions that initially appeared on the trunk and subsequently spread to the face, arms, and legs within two days, accompanied by pruritus and mild fever. The patient had no comorbidities or allergies, but a clear history of close contact with a classmate diagnosed with chickenpox was identified as the primary source of infection. Physical examination revealed multiple lesions at different stages of development without secondary bacterial infection, while vital signs remained stable. Therapeutic management included acyclovir, cetirizine syrup, paracetamol, and salicylic powder, combined with non-pharmacological interventions such as hygiene education, avoidance of scratching, adequate hydration, and temporary isolation to prevent transmission. Family-focused counseling emphasized the importance of monitoring for complications and maintaining supportive care. The patient responded favorably, with resolution of fever, reduction of pruritus, and crusting of lesions within one week. This study highlights the critical role of primary health centers in the early identification and management of varicella in pediatric populations. The novelty of this research lies in demonstrating how structured holistic diagnostics, timely antiviral therapy, and standardized family education can effectively reduce symptom burden, prevent complications, and limit community transmission. Such documentation provides valuable insights for strengthening clinical practice and public health preparedness in regions with uneven vaccine coverage.